2017
DOI: 10.1503/cmaj.160355
|View full text |Cite
|
Sign up to set email alerts
|

Use of azithromycin and risk of ventricular arrhythmia

Abstract: A zithromycin is a widely prescribed broad-spectrum macrolide used mainly for the treatment of respiratory and urinary tract bacterial infections. Concerns have been raised recently regarding its arrhythmogenic potential, a risk already known to be associated with the first marketed macrolide, erythromycin.1-6 Several case reports have described QTinterval prolongation, 7-9 torsades de pointes 10-12 and polymorphic ventricular tachycardia 13 following use of azithromycin. Many observational studies have report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 31 publications
(39 reference statements)
2
46
1
Order By: Relevance
“…13 In contrast, Svanstrom et al demonstrated no increased risk of death from cardiovascular causes from azithromycin in a large population of middle-aged adults in Denmark, compared with penicillin V, 10 and Trifiro et al found no risk of ventricular arrhythmia (VA) from azithromycin when compared with amoxicillin. 15 The divergent findings noted in the previously described studies may be attributable to differences in study populations. The increased risk associated with azithromycin has been most prominent in studies that included high-risk patients (eg, patients already experiencing cardiovascular diseases).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…13 In contrast, Svanstrom et al demonstrated no increased risk of death from cardiovascular causes from azithromycin in a large population of middle-aged adults in Denmark, compared with penicillin V, 10 and Trifiro et al found no risk of ventricular arrhythmia (VA) from azithromycin when compared with amoxicillin. 15 The divergent findings noted in the previously described studies may be attributable to differences in study populations. The increased risk associated with azithromycin has been most prominent in studies that included high-risk patients (eg, patients already experiencing cardiovascular diseases).…”
mentioning
confidence: 79%
“…In another study, Chou et al found cardiac risk not only for macrolides, but also for fluoroquinolones, when compared with amoxicillin‐clavulanate use . In contrast, Svanstrom et al demonstrated no increased risk of death from cardiovascular causes from azithromycin in a large population of middle‐aged adults in Denmark, compared with penicillin V, and Trifiro et al found no risk of ventricular arrhythmia (VA) from azithromycin when compared with amoxicillin …”
Section: Introductionmentioning
confidence: 99%
“…Other groups have been investigating a variety of data mining methodologies to query health records for identification of ADRs based primarily on clinical features . One notable effort is the Sentinel Initiative funded by the United States Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have been investigating a variety of data mining methodologies to query health records for identification of ADRs based primarily on clinical features. [11][12][13][14][15][16] One notable effort is the Sen- 11,20,21 Our dataset had limited structured diagnostic coding, which made it challenging for us to explore algorithms that rely on codes such as ICD-9.…”
Section: Negative Controlsmentioning
confidence: 99%
“…QTc altered after trimethroprim-sulfamethoxazole may be rare [53]. Two studies on non-septic patients [54,55] showed no difference in the incidence of arrhythmia between different groups of macrolides, indicating that illness severity is probably the most important factor. A recent meta-analysis found no significant potential for provoking arrhythmias in macrolides [56].…”
Section: Medicationmentioning
confidence: 99%